Efficacy of Rapid Salivary C-Reactive Protein Test to Assess Early Changes in Malignancy in the Oral Cavity and Its Utility in Screening for Oral Cancer - Vathsala Patil; Ravindranath Vineetha; Komal Smriti; Kalyana Chakravarthy Pentapati; Srikanth Gadicherla; Carnelio Sunitha (Dentistry Journal)
Background/Objectives: The present study aimed to test the efficacy of the chair-side rapid salivary C-reactive protein assay kit in differentiating oral potentially malignant disorders (OPMDs) and oral cancer from normal mucosa using whole salivary samples. Methods: In this study, unstimulated saliva samples of cases (OPMDs and oral cancer) and controls (systemically healthy subjects) were used to detect CRP levels using a novel colorimetric, quantitative rapid assay kit. Kruskal–Wallis ANOVA with a post hoc Dunn’s test were applied to determine the difference in the mean and SD values between the case and control groups. ROC analysis was performed to identify the positive and negative likelihood ratios. Results: The mean calculated salivary CRP level in the oral cancer group was 4.21 ng/mL, in the OPMD group it was 2.51 ng/mL and in the healthy controls it was 0.7 ng/mL. Post hoc tests showed that the salivary CRP levels were significantly higher in the oral cancer and OPMD groups than in the controls. Conclusions: The present study showed that the novel rapid salivary test kit could significantly differentiate between the salivary CRP values of cases and controls but there was no significant difference between the OPMD and malignancy groups. It also showed higher sensitivity values, confirming the efficacy of this kit as a screening tool.